SIMULATING LANDUSE CHANGES DRIVEN BY A 3rd BOSPHORUS BRIDGE - Ayazli, I. E.; Batuk, F.; Kleinschmit, B. (COPERNICUS GESELLSCHAFT MBH, 2010)
Istanbul, which joins two continents-Asia and Europe, is an important city with its cultural, natural and environmental heritages. In the past and today, increasing population has caused an enormous transportation problem. To overcome this problem, two bridges were built on the Bosphorus and a third bridge will be built on the north side of Bosphorus. Although zone plans made in the 1960s suggested the urban growth to east-west direction, urbanization was triggered to northward by Bosphorus Bridges. Main research questions of this study are: What is the influence of a third Bridge on urbanization processes in Istanbul? Which protected areas will be damaged? To find out the influences of 3rd Bosphorus Bridge on the urbanization in Istanbul, four Landsat satellite images were classified. First bridge was built on the Bosporus in 1973 and the second bridge in 1988. Therefore, time periods of the images were determined as 1972, 1987, 2002 and 2009. SLEUTH simulation software was used to predict the urban sprawl of Istanbul for the year 2030. The result of the prediction map was shown that 28.88 % forest and 71.43 % agricultural areas and open spaces will be transformed to urban area.
Keywords: Spatio-temporal Geodatabases; Urban Sprawl; Remote Sensing; Cellular Automata; Simulation; Physical Geography; Imaging Science & Photographic Technology